2022
DOI: 10.32604/cmc.2022.019586
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Hand Gesture Recognition Using 3D-CNN and LSTM Networks

Abstract: Recognition of dynamic hand gestures in real-time is a difficult task because the system can never know when or from where the gesture starts and ends in a video stream. Many researchers have been working on visionbased gesture recognition due to its various applications. This paper proposes a deep learning architecture based on the combination of a 3D Convolutional Neural Network (3D-CNN) and a Long Short-Term Memory (LSTM) network. The proposed architecture extracts spatial-temporal information from video se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Recently, deep learning has emerged as one of the techniques to be used for image processing tasks. It has been found that it produces significant outcomes in different fields, including agriculture [ 10 ], medicine [ 11 , 12 ], gesture recognition [ 13 ], and remote sensing [ 14 ], etc. In the medical field, it is used for the detection and classification of different diseases, including skin diseases [ 15 , 16 ], different types of ulcers, and cancer [ 17 ], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, deep learning has emerged as one of the techniques to be used for image processing tasks. It has been found that it produces significant outcomes in different fields, including agriculture [ 10 ], medicine [ 11 , 12 ], gesture recognition [ 13 ], and remote sensing [ 14 ], etc. In the medical field, it is used for the detection and classification of different diseases, including skin diseases [ 15 , 16 ], different types of ulcers, and cancer [ 17 ], etc.…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of applications, involving smart homes, video surveillance, sign language recognition, human–robot interaction, and health care, have recently embraced dynamic hand gestures. All of these applications require high levels of accuracy against a busy background, optimum recognition, and temporal precision (Huenerfauth and Lu, 2014 ; Ur Rehman et al, 2022 ).…”
Section: Techniques For Multimodal Human–robot Interactionmentioning
confidence: 99%
“…The issue with detecting an object in an image is obtaining a region, suggesting, and testing it according to the class of object. As a result, some researchers relied on a single approach to identify the object in the image as in the studies [18][19][20]. While others used a mix of two approaches as in the studies [21][22][23][24].…”
Section: Related Workmentioning
confidence: 99%